A study of early childhood English language development as an impact of English cartoons - Saiddina, Dinda Syifa; Darma, Virga Putra (Journal of Research on English and Language Learning (J-REaLL), 2024)
In this sophisticated era, technological advances have contributed to the phenomenon of bilingualism. Easy access to various content on the internet and social media has a new impact on the language acquisition of an individual, including children. Children are active users who access digital content, including English cartoons. Research conducted by Trota et al. (2022) and Alghonaim (2019) shows a significant effect of English cartoons on children's English language acquisition. Departing from this, the researcher conducted further research on similar influences on children who had mastered two languages before being exposed to English cartoons. Data was collected through direct observation and interviews with parents of participants. The research was conducted in Sarabau village, Plered sub-district, Cirebon district, with children aged 5 to 6 years as the object of research. The data was then carefully analyzed using a qualitative descriptive method. The results showed an influence on the acquisition of sound systems, vocabulary, and sentence formation in English. In line with this, researchers also found factors such as the intensity of screen time and the role and involvement of parents in the process of English language acquisition through English cartoons.